Optical size effects in thin gold films - Kovalenko, S.A.; Lisitsa, M.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
The optical size effects that appear in thickness dependencies of refraction (n) and absorption (k) indexes, Brewster's quasiangle and dielectric constant e2 in thin gold films are discussed. All of them have oscillating features in the range of thicknesses 20 < d < 180 A. The errors of determining the optical constants from the photometric data were carefully analyzed.